Find the inverse of y = (5x-4) / (2x+3)

the aim of finsing the inverse is making x the subject. To start we need to multiply both sides by: (2x+3), giving us:

y(2x+3) = 5x-4

now we need to expand the brackets:

2xy +3y = 5x-4

now gather all the x components on the same side:

2xy - 5x = -4-3y

now factorise the left hand side:

x(2y-5) = -4-3y

now make x the subject, giving us:

x =(-4-3y) / (2y-5)

therefore, the inverse is written in terms of x, which gives us:

f-1(x) = (-4-3y) / (2y-5)

Answered by Xuanyi A. Maths tutor

4939 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find the sum and product of the roots of the equation 2x^2+3x-5=0


Given y=rootx + 4/rootx = 4, find the value of dy/dx when x=8, writing your answer in the form aroot2, where a is a rational number.


How do you find a turning point of a function using differentiation?


Find the derivative of the function y=3x^2e^(2x)sin(x).


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences